2017
DOI: 10.1038/s41598-017-14862-3
|View full text |Cite
|
Sign up to set email alerts
|

A network meta-analysis on the beneficial effect of medical expulsive therapy after extracorporeal shock wave lithotripsy

Abstract: We applied a newly introduced method, network meta-analysis, to re-evaluate the expulsion effect of drugs including tamsulosin, doxazosin, nifedipine, terazosin and rowatinex after extracorporeal shock wave lithotripsy (ESWL) as described in the literature. A systematic search was performed in Medline, Embase and Cochrane Library for articles published before March 2016. Twenty-six studies with 2775 patients were included. The primary outcome was the number of patients with successful stone expulsion. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Medical expulsive therapy (MET) was used for promoting the spontaneous passage of stone fragment after ESWL and reducing the stone expulsion time and analgesic requirements (4)(5)(6). Nowadays, tamsulosin is the most common agents used in adjunctive MET after ESWL with large amount of relevant published studies (7). However, some randomized controlled trials (RCTs) showed conflicting results, especially for patients received ESWL for more than once.…”
Section: Introductionmentioning
confidence: 99%
“…Medical expulsive therapy (MET) was used for promoting the spontaneous passage of stone fragment after ESWL and reducing the stone expulsion time and analgesic requirements (4)(5)(6). Nowadays, tamsulosin is the most common agents used in adjunctive MET after ESWL with large amount of relevant published studies (7). However, some randomized controlled trials (RCTs) showed conflicting results, especially for patients received ESWL for more than once.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the results of SWL and obtain a better stone-free rate, many institutions have used medical expulsive therapy (MET) as an adjunctive treatment [ 7 ]. In the past few years, calcium channel blockers and alpha-1 adrenergic receptor antagonists have been the main established treatments of choice for MET [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it does show superiority currently. For patients, timely use of extracorporeal shock wave lithotripsy and the selection of reasonable lithotropic drugs are particularly important for the radical treatment of kidney stone (Yang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%